2019
DOI: 10.1111/jora.12448
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Relation Between Youths’ Perceived Spirituality and Indicators of Positive Development

Abstract: Using data from the 4‐H Study of Positive Youth Development (PYD), we employed a cross‐lagged model to examine the temporal order of the relationship between PYD and youths’ spirituality. Our sample consisted of 1,842 youth from 32 states in the continental United States. Mean age across the two waves of data used in this study was 15.5 and 16.6, respectively. The cross‐lagged model allowed us to test the model suggesting that youth must develop certain abilities (e.g., Cs of PYD) prior to constructing and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…Another observation is that compared to the previous findings that the magnitude of 1-year autoregressive coefficients for PYD and well-being constructs was around or higher than 0.60 (Yu and Shek, 2018;James and Ward, 2019), the temporal stability of PYD and well-being measures was not high (ranging between 0.34 and 0.48) in the present study. The relatively "lower" autoregressive coefficients in the present study can be explained by the fact that PYD, life satisfaction, and hopelessness are not stable trait-like constructs because they keep on developing during adolescence (Hamaker et al, 2015).…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…Another observation is that compared to the previous findings that the magnitude of 1-year autoregressive coefficients for PYD and well-being constructs was around or higher than 0.60 (Yu and Shek, 2018;James and Ward, 2019), the temporal stability of PYD and well-being measures was not high (ranging between 0.34 and 0.48) in the present study. The relatively "lower" autoregressive coefficients in the present study can be explained by the fact that PYD, life satisfaction, and hopelessness are not stable trait-like constructs because they keep on developing during adolescence (Hamaker et al, 2015).…”
Section: Discussioncontrasting
confidence: 92%
“…In addition, it is not uncommon to identify relatively lower autoregressive effects in cross-lagged models involving PYD and well-being factors. For example, Shek and Zhu (2019) reported a 1-year autoregressive coefficient around 0.40 for moral competence; Yu and Shek (2018) reported 1-year autoregressive coefficients ranging between 0.41 and 0.55 for hopelessness; and James and Ward (2019) reported a 1-year autoregressive coefficient of 0.18 for perceived spirituality. Similarly, the 2-year autoregressive coefficients of PYD-related constructs, such as self-efficacy and self-regulation, were around 0.30 in recent studies ( Tovel et al, 2019 ; Memmott-Elison et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…King et al (2011) noted that religious and spiritual contexts contain ideological (e.g., moral belief systems), social (e.g., sense of belongingness and acceptance), and transcendental (e.g., search for meaning and purpose) resources that other organizations may find challenging to cultivate (King et al, 2011). Indeed, past studies provide evidence on the role of faith‐based organizations in facilitating adolescent thriving characteristics such as the Five Cs of PYD (Bowers et al, 2020; Buenconsejo et al, 2022; Gomez‐Baya et al, 2022; James & Ward, 2019; Tirrell et al, 2019). For example, in a study conducted in El Salvador, young people enrolled in a Christian‐based program reported greater transcendence and character compared to those who were not enrolled in the program (Tirrell et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Positive associations were also observed between spiritual transcendence and the Five Cs among Filipino adolescents, with connection exhibiting the highest correlations with it (Buenconsejo et al, 2022). Interestingly, examining the temporal relations between PYD and spirituality among North American adolescents, James and Ward (2019) found that while PYD predicted subsequent spirituality, spirituality did not predict subsequent PYD levels.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies suggest that religiosity has a significant influence on adolescent behavior ( Salas-Wright et al, 2017 ; Holmes et al, 2019 ; James and Ward, 2019 ). However, according to some authors, “If researchers use only one domain of religiosity, they likely will fail to capture the collective influence of religiosity on risky sexual behavior” ( Smith, 2015 , p. 51).…”
Section: Introductionmentioning
confidence: 99%